Experiência inicial com o uso da reserva fracionada de fluxo na avaliação hemodinâmica da estenose da artéria do rim transplantado - Gomes Junior, Manuel Pereira Marques [UNIFESP] (2019)
Objective: To describe and standardize an original protocol for fractional flow reserve (FFR) pre and post angioplasty in an initial series of patients with clinically manifested transplant renal artery stenosis (TRAS) and angiographically severe obstructive lesions. To evaluate correlations between FFR data and angiographic measurements and other previously validated hemodinamyc parameters on stenosis functional repercussion evaluation. Background: There is no data in the literature about the use of FFR in TRAS. Methods: Patients with TRAS detected in a non-invasive study were referred to diagnostic angiography and stenosis considered visually severe (≥60%) were managed with stent angioplasty. After selective cannulation of the transplanted renal artery, a PressureWire 0.014 (Certus™ - St. Jude Medical) was advanced to the distal portion of the vessel. Resting Pd/Pa ratio (ratio of mean distal to lesion to proximal pressure) and translesional pressure gradients were obtained and FFR and hyperemic translesional systolic and mean pressure gradients (HSG and HMG) were registered after papaverine induced maximum hyperemia- pre and post stent implantation. Creatinine levels and office blood pressure measurements were registered at the baseline, 6 and 12 months after intervention. Student’s t test for parallel sample and ANOVA were used for comparison among different moments. Pearson’s correlations between pre-intervention FFR and angiographic or hemodynamic measurements, was also applied. Results: Ten consecutive patients had successful stent implantation and were included in the study. Graft dysfunction was present in 90% and resistant hypertension in 50%. Average time of transplantation was 11 ± 7 months. Significant elevation in translesional systolic pressure gradient (52.3 + 18.76 vs 60.3 + 17.8 mmHg) and reduction in Pd/Pa ratio (0.8 + 0.09 vs 0.77 + 0.09) were observed after papaverine infusion (p<0.001 for both). After treatment, significant increase in FFR (0.96 ± 0.04 p<0.001) and reduction in systolic hyperemic gradients (-41.40 ± 19.18, p<0,001) and mean (-24.00 ± 11.65, p<0.001) were observed. A strong negative correlation was observed between FFR and percent stenosis diameter-%SD (r= -0.89, p<0.001) and HSG (r=-0.9, p<0.001) as well as a strong positive correlation between FFR and baseline Pd/Pa ratio (r=0.9, p<0.001). No complications occurred during papaverine infusion or stent implantation. Baseline creatinine levels (1.61 ± 0.17 mg/dl) after 6 months (1.79 ± 0.17 mg/dl) and after 1 year of treatment (1.84 ± 0.20 mg/dl, p = 0.073) were similar. A significant reduction in systolic blood pressure was observed in outpatient follow-up at 6 (mean of 14.8 mmHg, p<0.001) and 12 months (mean 20 mmHg, p<0.001). There was also a significant reduction in the number of antihypertensive drugs in the same intervals (p=0.005). Conclusion: FFR proved to be a valid and well tolerated method during percutaneous intervention in EART. A good correlation was observed between FFR and other hemodynamic parameters also used to determine the functional repercussion of stenoses. The application of this method before intervention in the evaluation of moderate or ambiguous stenosis should be stimulated. A possible correlation between the outcome of percutaneous interventions for functionally significant stenoses and their association with the clinical response to treatment should be further explored.